If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -39 + -2x = 7x + -6(1 + 7x) -39 + -2x = 7x + (1 * -6 + 7x * -6) -39 + -2x = 7x + (-6 + -42x) Reorder the terms: -39 + -2x = -6 + 7x + -42x Combine like terms: 7x + -42x = -35x -39 + -2x = -6 + -35x Solving -39 + -2x = -6 + -35x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35x' to each side of the equation. -39 + -2x + 35x = -6 + -35x + 35x Combine like terms: -2x + 35x = 33x -39 + 33x = -6 + -35x + 35x Combine like terms: -35x + 35x = 0 -39 + 33x = -6 + 0 -39 + 33x = -6 Add '39' to each side of the equation. -39 + 39 + 33x = -6 + 39 Combine like terms: -39 + 39 = 0 0 + 33x = -6 + 39 33x = -6 + 39 Combine like terms: -6 + 39 = 33 33x = 33 Divide each side by '33'. x = 1 Simplifying x = 1
| X^2+6x=59 | | 8v=2(4v+-2) | | -3x+50=2x+10 | | -12=-2(x+5) | | In(2x)=-2 | | 4-7x+6x=0 | | t=(x-7)(2+y) | | 9m=6(a+4) | | -19=2+4(h+7) | | 754/1000000 | | 3x(2x-3)=27 | | 17j-6=14j+7 | | 18.24=-16t^2+24t+8 | | 3n-9=2n+13 | | 8-6n=-7+5(5n+3) | | 7i/8i | | -8x+y=50 | | x-12/5=-6 | | 7-(2-y)=-4 | | 18.24=-16t+24t+8 | | x+39-3x-40=949 | | 9*45=5(f-32) | | (n-12)*8=80 | | x+x+37+4x-40=819 | | 19-5x=7x+19 | | -3y-27=-6(y+6) | | t=(x+y)(2x-y) | | 5*(x-2)=2+2x+x+4 | | 0=5x^2+15 | | 7x-32+3x+12=180 | | -24x=7x-4 | | (n-8)*8=32 |